E-079 Retrospective multicentre analysis of treatment strategies and outcomes with Solitaire FF for acute ischaemic stroke after FDA approval. (14th July 2013) - Mokin, M; Dumont, T; Veznedaroglu, E; Binning, M; Liebman, K; Fessler, R; To, C Yuen; Turner, R; Turk, A; Chaudry, I; Arthur, A; Fox, B; et al.
Abstract : Background: The promising results of the Solitaire FR With the Intention for Thrombectomy (SWIFT) trial recently led to Food and Drug Administration (FDA) approval of the Solitaire FR stent retriever device for recanalisation of cerebral vessels in patients with acute ischaemic stroke. Objective: To report the early postmarket experience with this device since its FDA approval in the United States, which has not been previously described. Methods: We conducted a retrospective analysis of consecutive acute ischaemic strokes cases treated between March 2012 and July 2012 at 10 United States centres where the Solitaire FR used as a single device or in conjunction with other intraarterial endovascular approaches. Results: A total of 101 patients were identified (mean age, 64.7 years; mean admission National Institutes of Health Stroke Scale [NIHSS] score, 17.6). Intravenous thrombolysis was administered in 39% of cases; other endovascular techniques were utilised in conjunction with the Solitaire FR in 52%. Successful recanalisation (Thrombolysis in Myocardial Infarction 2/3) was achieved in 88%. The rate of symptomatic intracranial haemorrhage within the first 24 hours was 15%. In-hospital mortality was 26%. At 30 days, 38% of patients had favourable functional outcome (modified Rankin scale score ≤2). Severity of NIHSS score on admission was a strong predictor of poor outcome. Conclusion: Our study shows that a variety of other endovascular approaches are used in conjunction with Solitaire FR in actual practice in the United States. Early postmarket results suggest that Solitaire FR is an effective tool for endovascular treatment of acute ischaemic stroke. Disclosures: M. Mokin: 1; C; Toshiba Educational Research Grant. T. Dumont: None. E. Veznedaroglu: None. M. Binning: None. K. Liebman: None. R. Fessler: None. C. Yuen To: None. R. Turner: None. A. Turk: None. I. Chaudry: 2; C; ev3/Covidien, Microvention. A. Arthur: 2; C; Covidien, J&J, Stryker, Terumo. B. Fox: None. R. Hanel: None. R. Tawk: None. P. Kan: None. G. Lanzino: None. D. Lopes: None. M. Chen: None. R. Moftakhar: None. J. Billingsley: None. A. Ringer: 2; C; ev3/Covidien, Stryker. K. Snyder: 2; C; Toshiba. 3; C; ev3/Covidien, The Stroke Group. N. Hopkins: 2; C; Abbott, Boston Scientific, Cordis, Micrus, W. L. Gore. 3; C; Abbott Vascular. 6; C; St. Jude Medical, Toshiba, AccessClosure, Augmenix, Boston Scientific, Claret Medical, Micrus, Valor Medical, Boston Scientific, Cleveland Clinic, Complete Conference Management, Cordis, SCAI. A. Siddiqui: 2; C; Codman & Shurtleff, Concentric Medical, ev3/Covidien Vascular Therapies, GuidePoint Global Consulting, Penumbra. 3; C; Codman & Shurtleff, Genentech. 6; C; Hotspur, Intratech Medical, StimSox, Valor Medical. E. Levy: 1; C; Boston Schientific, Codman & Shurtleff, ev3/Covidien Vascular Therapies. 2; C; Codman & Shurtleff; ev3/Covidien Vascular Therapies, TheraSyn Sensors. 4; C; Intratech Medical, Mynx/Access Closure. 6; C; Abbott Vascular, ev3/Covidien Vascular Therapies.